2018
DOI: 10.1002/jmri.26531
|View full text |Cite
|
Sign up to set email alerts
|

MR‐Based Radiomics Nomogram of Cervical Cancer in Prediction of the Lymph‐Vascular Space Invasion preoperatively

Abstract: Background Lymph‐vascular space invasion (LVSI) is an unfavorable prognostic factor in cervical cancer. Unfortunately, there are no current clinical tools for the preoperative prediction of LVSI. Purpose To develop and validate an axial T 1 contrast‐enhanced (CE) MR‐based radiomics nomogram that incorporated a radiomics signature and some clinical parameters for predicting LVSI of cervical cancer preoperatively. Study Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 38 publications
2
57
3
1
Order By: Relevance
“…First, the optimal radiomics features were put into a logistic regression model to obtain the regression coefficients . Then the Rad_Score of each patient was calculated using a linear combination of these selected features with their corresponding regression coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the optimal radiomics features were put into a logistic regression model to obtain the regression coefficients . Then the Rad_Score of each patient was calculated using a linear combination of these selected features with their corresponding regression coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…First, the optimal radiomics features were put into a logistic regression model to obtain the regression coefficients. 32 Then the Rad_Score of each patient was calculated using a linear combination of these selected features with their corresponding regression coefficients. Finally, the Rad_Score and the clinical potential factors in the training cohort were analyzed using the univariate and multivariate regression to select the independent predictors.…”
Section: Performance Evaluation Using Both Radiomics Features and CLImentioning
confidence: 99%
“…According to Hua et al [33], the model based on multiparametric MRI showed the best prediction results, with an AUC of 0.842 (95% CI, 0.772-0.913; sensitivity = 0.773; speci city = 0.776) in the training cohort and 0.775 (95% CI, 0.637-0.912; sensitivity = 0.739; speci city = 0.667) in the validation cohort. Similarly, Li et al [34] also found that the radiomics nomogram derived from MRI showed favorable discrimination between LVSI and non-LVSI groups, with an AUC of 0.754 (95% CI, 0.6326-0.8745) in the training cohort and 0.727 (95% CI, 0.5449-0.9097) in the validation cohort. We initially used the combination of PET radiomics with protein molecule to predict LVSI, which showed that the radiomics and combined models based on 18 F-FDG PET imaging showed better results than those of previous studies.…”
Section: Discussionmentioning
confidence: 76%
“…LNM is an intricate biological process in AGC, in which the primary tumor lesions undoubtedly play an important role (1416). Jiang's study (4) established a radiomic nomogram based on CT images and clinicopathological findings to estimate the LNM in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%